PENCIPTAAN KARYA TEATER PAKELIRAN SASTRA RUPA “JAPA TUAN” - Gunayasa, I Wayan; Hendro, Dru; Sudarta, I Gusti Putu (JURNAL DAMAR PEDALANGAN, 2025)
This research-creation explores the development of the Teater Pakeliran Sastra Rupa “Japa Tuan” as an innovative model of Balinese shadow theatre that recontextualizes the classical gaguritan Japa Tuan into a contemporary performative form. The study aims to demonstrate how local Balinese literary sources can be transformed into theatrical works that maintain spiritual depth while responding to the aesthetic demands of modern audiences. The creative process was framed by the Asta Widhi Kawya method, adapted within the MBKM (Merdeka Belajar Kampus Merdeka) scheme, encompassing conceptual contemplation, narrative structuring, vocal and movement exploration, symbolic embodiment, and final staging. The results reveal that the story of Japa Tuan—depicting spiritual quest, grief, and transcendence—was successfully embodied through the integration of vocal performance, silhouette theatre, wayang manipulation, ritualized movement, and symbolic scenography. The artistic outcome emphasizes both the sacred and aesthetic dimensions, producing a hybrid form that remains rooted in Balinese cultural philosophy while offering an alternative format of contemporary pedalangan. The novelty of this work lies in its use of gaguritan as a dramaturgical foundation and its synthesis of textual, visual, and spiritual elements. This creation contributes to the revitalization of traditional arts, the enrichment of academic discourse in performing arts, and the affirmation of Balinese cultural identity in a global context.